2020
DOI: 10.1177/2399202620940267
|View full text |Cite
|
Sign up to set email alerts
|

A model to strengthen utility of quality pharmaceutical health systems data in resource-limited settings

Abstract: Background: Limited utility of quality health data undermines efforts to strengthen healthcare delivery, particularly in resource-limited settings. Few studies model the effective utility of quality pharmaceutical information system (PIS) data in sub-Saharan Africa, typified with weak health systems. Aim: To develop a model and guidelines for strengthening utility of quality PIS data in public healthcare in Namibia, a resource-limited setting. Methods: A qualitative model based on Dickoff et al. practice-orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Pharmacy personnel at different supply chain levels should receive intensive training on inventory management and SOPs to maximize performance on on-time recording of transactions on FESC, placing orders accurately, reducing volumes of expiry, and lowering the rates of stock-outs of pharmaceuticals. 3,9,11 The majority of the respondents (72.9%) agreed that trained staff availability is an important factor in the improvement of the inventory management and SOPs compliance. Most pharmacy staff did not receive adequate training on inventory management at the facility level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pharmacy personnel at different supply chain levels should receive intensive training on inventory management and SOPs to maximize performance on on-time recording of transactions on FESC, placing orders accurately, reducing volumes of expiry, and lowering the rates of stock-outs of pharmaceuticals. 3,9,11 The majority of the respondents (72.9%) agreed that trained staff availability is an important factor in the improvement of the inventory management and SOPs compliance. Most pharmacy staff did not receive adequate training on inventory management at the facility level.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study done in Namibia has revealed that employees at the healthcare facility level do not always follow SOPs, nor appropriately document pharmaceutical transactions to generate relevant reports. 9 Standardized guidelines to register patients for rabies vaccination should be in place at each health facility level, and the number of rabies cases and dog-bite patients should be reported on-time to the NHIS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a concern during the current era of epidemics such as COVID-19, that requires efficient pharmaceutical supply chains and increased access to quality medicine for the public (Koehler & Brown 2017;Amimo, Lambert, & Magit 2020). Moreover, the burden of COVID-19 estimated at 1,727,837 cases in Africa and 12,675 in Namibia (as at midnight 26th August, 2020), has exposed the weak pharmaceutical systems in sub-Saharan Africa (Jernigan, 2020;Kagoya et al, 2020). Most African countries are unable to locally manufacture essential medicines, particularly those critical in the fight against…”
mentioning
confidence: 99%